KONSEP, TEORI, DAN KARAKTER KEPEMIMPINAN ORGANISASI - Danang Nugroho; Nuri Amanda Fitriani; Nur Fitri Intan Sari; Aldira Achmad Rizky; Adelia Asipa Pariza; Alicia Shafira Kurnia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Leadership is defined as the process by which an individual influences the behavior of others to achieve a goal. In this process, the leader utilizes power to influence the behavior of subordinates. Five types of power have been identified: (1) expert power, derived from knowledge or expertise, (2) legitimate power, obtained through formal position or authority, (3) referent power, stemming from personal influence or charisma, (4) reward power, associated with the ability to provide rewards, and (5) coercive power, based on the ability to administer punishment or coercion. Moreover, leadership is closely linked to individual characteristics. Numerous studies have attempted to identify consistent leadership traits, but such endeavors often encounter challenges. The most widely accepted findings from this research suggest that only certain characteristics can consistently be associated with leadership, while efforts to differentiate between leaders and followers, or between effective and ineffective leaders, often prove elusive.